Analysis of ionospheric storm‑time effects over the East African sector during the 17 March 2013 and 2015 geomagnetic storms - Habyarimana, Valence; Habarulema, John Bosco; Dugassa, Teshome (Earth, Planets and Space, 2023)
An analysis of the mechanisms that caused the storm-time effects during two geomagnetic storms that occurred on 17 March 2013 and 2015 is presented. We used Global Navigation Satellite System (GNSS) derived Total Electron Content (TEC) data over the trough (Addis Ababa, ADIS, 38.8◦ E geographic longitude, 0.18◦ N geomagnetic latitude) and near the crest (Mbarara, MBAR, 30.7◦ E geographic longitude, 10.22◦ S geomagnetic latitude) regions of East African sector. Magnetometer data over Addis Ababa (AAE) and Mbour (MBO) were also used to derive the disturbance in ionospheric currents during the two storm periods. The monthly median TEC values for a month within which the storm under consideration occurred were used as a measure of background variability to analyse the response of the ionosphere to the storms. The response of the ionosphere to a geomagnetic storm is considered to be significant when the magnitude of TEC deviation (|_TEC|) is ≥ 45%. During the storm main phase, the ionosphere over the East African trough responded positively to the 17 March 2015 geomagnetic storm at 1800 UT, whilst at the crest regions, there was no significant response to the two St. Patrick’s day geomagnetic storms. However, during the storm recovery phase of 17 March 2013 and 2015 storms, both the stations over the trough and crest regions of East Africa showed a positive response. We checked thermospheric [O]/ [N2] changes as a result of the two storms. There were no appreciable changes in [O]/ [N2] over this sector between 16 and 18 March 2013. We observed an appreciable change in [O]/ [N2] between 16 and 18 March 2015. The [O]/ [N2] increase was more pronounced/obvious on 18 March 2015. The positive ionospheric responses during the recovery phases of the two geomagnetic storms could not be attributed to changes in thermospheric [O]/ [N2] because the responses were nighttime features. The southward turning of the z component of Interplanetary magnetic field (IMF Bz) led to enhanced eastward equatorial electric field (EEF) during 0725 UT (1025 LT) and 0645 UT (0945 LT) for 17 March 2013 and 17 March 2015 storms, respectively. We note that when the IMF Bz turned northward, the EEF turned westward. During the southward turnings of IMF Bz that took place at about 1435 UT (1735 LT) on 17 March 2013, eastward prompt penetration electric field (PPEF) occurred in the post-sunset period starting at about 1600 UT (1900 LT) and enhanced the Prereversal enhancement (PRE). The presence of westward PPEF at around 1500 UT (1800 LT) acted to suppress the PRE on 17 March 2015. The positive storm effects during the recovery phases of the two storms may be attributed to strong disturbed dynamo electric field (DDEF), which was eastward during the night. We may thus surmise that the ionospheric responses to geomagnetic storms of St. Patrick’s day over the equatorial and low-latitude region of Africa were as a result of the combined effect of equatorward neutral wind, PPEF and DDEF.
Keywords: Ionospheric storms; Total electron content; Ionospheric currents; Geomagnetic storms; Prompt penetration electric field; Disturbed dynamo electric field